High-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material as well as preparation method and application thereof

By incorporating high-entropy alloy nanoparticles into PVA/PPy hydrogels, the material's light absorption, thermal management, and mechanical strength are enhanced, addressing the limitations of traditional water condensate materials and improving solar-driven water evaporation efficiency and stability.

CN120310050APending Publication Date: 2025-07-15DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510548425.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Traditional hydrogels have shortcomings in electrical conductivity, thermal stability and mechanical strength, which limit their long-term use performance in complex environments. In addition, traditional solar interface evaporator materials lack light absorption performance, poor thermal management capabilities, and low water evaporation efficiency.

Method used

High-entropy alloy nanoparticles are introduced into polyvinyl alcohol/polypyrrole composite hydrogel, and high-entropy alloy modified composite hydrogel materials are prepared through polymerization and freeze-drying, and the excellent performance of high-entropy alloys is used to improve the light absorption, thermal management and mechanical strength of the hydrogel.

Benefits of technology

It significantly improves the light absorption performance and thermal management capabilities of the hydrogel, improves mechanical strength and chemical stability, and achieves efficient photothermal conversion and water evaporation performance. It is suitable for solar-driven water purification and desalination technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120310050A_ABST
    Figure CN120310050A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material as well as a preparation method and application thereof. Firstly, a polypyrrole aqueous solution is prepared through chemical oxidative polymerization, and high-entropy alloy nanoparticles are synthesized through a Joule thermal technology; and then mixing a polypyrrole aqueous solution, the high-entropy alloy nanoparticles and a polyvinyl alcohol aqueous solution, and adding a cross-linking agent and a catalyst to prepare the high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material. According to the composite hydrogel, under the synergistic effect of the high-entropy alloy, the light absorption performance is remarkably improved, wide-spectrum efficient absorption of ultraviolet rays, visible light and near-infrared light in a solar spectrum is achieved, and meanwhile the mechanical strength and chemical stability of the material are enhanced. The preparation process is simple, the cost is low, and the prepared composite hydrogel has wide application prospects in the fields of seawater desalination, wastewater treatment and the like as a solar interface evaporator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular, to a polyvinyl alcohol / polypyrrole composite hydrogel material modified by a high-entropy alloy, and a preparation method and application thereof. Background Art

[0002] The problem of global water resource shortage is becoming increasingly severe. As a sustainable means of water purification and desalination, the technology of interfacial evaporation driven by high-efficiency solar energy has received extensive attention. However, the materials of traditional solar interfacial evaporators are limited in their practical application effects due to problems such as insufficient light absorption performance, poor thermal management ability, and low water evaporation efficiency. In recent years, hydrogels have become an interfacial evaporator material that has received much attention due to their good hydrophilicity, biocompatibility, and three-dimensional network structure. However, hydrogels still have deficiencies in conductivity, thermal stability, and mechanical strength, which limit their long-term use performance in complex environments.

[0003] At present, there have been research reports on improving the performance of hydrogels by modifying them with single metals or alloys. For example, by embedding metal nanoparticles (such as zinc oxide nanoparticles) or magnetic metal nanoparticles, the conductivity and response performance of hydrogels can be enhanced. However, these modified hydrogels still have the following defects: insufficient conductivity, the conductivity of single metals or alloys is limited and difficult to meet the requirements of efficient photothermal conversion; poor thermal stability, under high temperature or extreme environments, the thermal stability of hydrogels is insufficient, which may lead to performance degradation; low mechanical strength, the mechanical strength and durability of the modified hydrogels still need to be further improved.

[0004] High-entropy alloys are formed by the random distribution of multiple metal elements to form a complex crystal structure, showing excellent conductivity, thermal stability, and mechanical strength. The excellent properties of high-entropy alloys mainly stem from the following aspects: lattice distortion effect, due to the random distribution of multiple metal elements in high-entropy alloys, the crystal structure is distorted, thus significantly improving its mechanical strength and hardness; cocktail effect, the interaction between different elements makes high-entropy alloys exhibit a composite effect, enhancing their conductivity, thermal stability, and corrosion resistance; slow diffusion effect, the diffusion coefficient of elements in high-entropy alloys is low, reducing the heat dissipation to the surrounding environment, thereby improving the thermal management ability; high-entropy effect, the high-entropy state of high-entropy alloys enables them to maintain good performance under extreme conditions, breaking through the performance limits of traditional materials.

[0005] If high-entropy alloy nanoparticles are introduced into the hydrogel, it is speculated that the light absorption performance of the hydrogel can be significantly improved, enabling it to absorb ultraviolet, visible, and near-infrared light in the solar spectrum more efficiently and achieve efficient photothermal conversion. At the same time, the introduction of high-entropy alloy may enhance the thermal management ability of the hydrogel, reduce heat dissipation, and improve the mechanical strength and chemical stability of the hydrogel, enabling it to maintain efficient water evaporation performance during long-term use. In addition, the addition of high-entropy alloy nanoparticles may also improve the mechanical strength and chemical stability of the hydrogel, enabling it to maintain efficient water evaporation performance during long-term use.

[0006] Currently, there are no research reports on the combination of high-entropy alloy nanoparticles and hydrogels. This innovative combination is expected to break through the performance bottleneck of traditional materials and provide an efficient, stable, and sustainable solution for solar-driven water purification and desalination technologies. Summary of the Invention

[0007] The object of the present invention is to provide a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material, its preparation method and application. By introducing high-entropy alloy nanoparticles into the polyvinyl alcohol / polypyrrole (PVA / PPy) composite hydrogel, a solar interface evaporator with efficient light absorption, excellent thermal management, and high water evaporation efficiency is prepared, effectively solving the deficiencies of traditional materials and promoting the practical application of solar-driven interface evaporation technology.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] On the one hand, the present invention provides a preparation method of a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material, including the following steps:

[0010] S1: Dissolve ammonium persulfate in deionized water, and after mixing evenly, obtain an ammonium persulfate solution; mix pyrrole monomer with deionized water to obtain a pyrrole solution. Under continuous stirring conditions, drop the ammonium persulfate solution and the pyrrole solution into hydrochloric acid solution for polymerization reaction. After the reaction is completed, dry and grind to obtain polypyrrole powder, and dissolve the polypyrrole powder in deionized water, and after mixing evenly, obtain a polypyrrole aqueous solution;

[0011] S2: Add iron salt, cobalt salt, nickel salt, manganese salt, zinc salt, copper salt and carbon nanotubes to deionized water and absolute ethanol, stir and mix evenly to obtain a high-entropy alloy precursor solution;

[0012] S3: Heat and stir the high-entropy alloy precursor solution obtained in step S2 to evaporate the solvent, and then perform freeze-drying to obtain a high-entropy alloy precursor powder. Take the high-entropy alloy precursor powder, wrap it with carbon paper, and heat it using Joule heat technology to obtain high-entropy alloy nanoparticles;

[0013] S4: Mix the aqueous solution of polyvinyl alcohol, the aqueous solution of polypyrrole obtained in step S1, and the high-entropy alloy nanoparticles obtained in step S3, add glutaraldehyde solution and hydrochloric acid solution to obtain a precursor of the composite hydrogel material;

[0014] S5: Let the composite hydrogel precursor obtained in step S4 stand overnight, then freeze it, and then thaw it. Repeat the freeze-thaw cycle multiple times, and finally obtain a high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel material after freeze-drying.

[0015] Further, in step S1, the concentration of the aqueous solution of polypyrrole is 8-15 wt%.

[0016] Further, in step S2, the iron salt, cobalt salt, nickel salt, manganese salt, zinc salt, and copper salt are selected from one of sulfates, nitrates, and chlorides; the volume ratio of deionized water to absolute ethanol is 1:1-3:1.

[0017] Further, in step S3, the conditions for heating using the Joule heating technique are: first heat at 300-800 °C for 0.5-3 s, and then heat at 1000-1500 °C for 1-5 s;

[0018] The chemical formula of the high-entropy alloy nanoparticles is Co a Cu b Fe c Mn d Ni e Zn f , where a, b, c, d, e, and f are the molar fraction percentages of the six elements in the total metal content. a is 26%-31%, b is 20%-25%, c is 5%-10%, d is 3%-6%, e is 35%-40%, f is 0.5%-2%, and the sum of a, b, c, d, e, and f is 100%.

[0019] Further, in step S4, the preparation method of the aqueous solution of polyvinyl alcohol is: add polyvinyl alcohol to deionized water and stir at 70-90 °C to obtain an aqueous solution of polyvinyl alcohol.

[0020] Further, in step S4, the concentration of the polyvinyl alcohol solution is 8-15 wt%.

[0021] Further, in step S4, in the mixed solution, the mass ratio of polypyrrole to polyvinyl alcohol is 1:8-1:12, and the mass ratio of high-entropy alloy nanoparticles to polypyrrole is 1:5-1:15.

[0022] Further, in step S5, the freezing temperature is -10 to -40°C, the freezing time is 2 to 3 h, the thawing temperature is 20 to 40°C, the thawing time is 0.5 to 1 h, and the freeze-thaw cycle times are 2 to 5 times.

[0023] Further, in step S5, the freeze-drying time is 12 to 24 h.

[0024] On the other hand, the present invention provides an application of the composite hydrogel material prepared by the above preparation method in a solar interface evaporator.

[0025] The beneficial effects of the present invention are as follows:

[0026] 1. By combining high-entropy alloy nanoparticles with the hydrogel, the present invention significantly improves the light absorption performance of the hydrogel. High-entropy alloy nanoparticles have a local surface plasmon resonance effect and a topological surface state synergy effect, which can effectively absorb ultraviolet light, visible light, and near-infrared light in the solar spectrum. Its complex crystal structure composed of multiple elements further enhances the broadband characteristics of light absorption, significantly increasing the average absorption rate of the material in the wavelength range of 250–2500 nm, thereby achieving efficient photothermal conversion.

[0027] 2. The introduction of the high-entropy alloy in the present invention enhances the thermal management ability of the hydrogel. The high-entropy alloy has a low thermal diffusion coefficient (slow diffusion effect), which can significantly reduce the heat dissipation to the surrounding environment. At the same time, its high thermal conductivity promotes the rapid transfer of photothermal energy, enabling the heat to be efficiently concentrated at the evaporation interface, thereby further improving the water evaporation efficiency.

[0028] 3. The addition of high-entropy alloy nanoparticles improves the mechanical strength and chemical stability of the hydrogel. The lattice distortion effect and cocktail effect of the high-entropy alloy enhance the anti-deformation ability and corrosion resistance of the material. In addition, the high-entropy state of the high-entropy alloy enables it to maintain good performance under extreme conditions, significantly improving the chemical stability of the composite material.

[0029] 4. The preparation method of the present invention is simple and the process is controllable. The solar interface evaporator based on the composite material is applicable to fields such as seawater desalination and wastewater treatment, and has broad application prospects. Description of the Drawings

[0030] Figure 1 Scanning electron microscope image of the high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel prepared in Example 1;

[0031] Figure 2 X-ray diffraction pattern of the high-entropy alloy nanoparticles in Example 1;

[0032] Figure 3The light absorption performance of the high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel prepared in Example 1 in the wavelength range of 280 - 2500 nm;

[0033] Figure 4 The evaporation rate of the high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel prepared in Example 1 under different light intensities;

[0034] Figure 5 For Examples 1 - 6, the evaporation rate of the high-entropy alloy-modified polyvinyl alcohol / polypyrrole hydrogel under a light intensity of 1 kW / m 2 Light intensity. Detailed implementation mode

[0035] The present invention will be further described below in conjunction with specific embodiments. The materials involved in the present invention are not limited to the descriptions in the following embodiments.

[0036] Unless otherwise specified, the raw materials in the embodiments of the present invention are all purchased through commercial channels.

[0037] Example 1

[0038] Prepare a high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel material according to the following steps:

[0039] S1: Dissolve 0.228 g of ammonium persulfate (APS) in 10 mL of deionized water, and ultrasonically treat for 10 min to obtain an APS solution. Mix 0.069 mL of pyrrole monomer with 10 mL of deionized water, and ultrasonically treat for 10 min to obtain a pyrrole solution. Under stirring conditions, drop the APS solution and the pyrrole solution into 50 mL of 1.2 M HCl aqueous solution, polymerize for 5 min, dry and then grind to obtain polypyrrole (PPy) powder. Dissolve 0.1 g of PPy powder in 0.9 ml of deionized water, and mix evenly to obtain a 10 wt% PPy aqueous solution;

[0040] S2: Mix 199.96 mg of ferric sulfate, 77.50 mg of cobalt sulfate, 77.38 mg of nickel sulfate, 75.51 mg of manganese sulfate, 80.73 mg of zinc sulfate, 79.81 mg of copper sulfate, and 50 mg of carbon nanotubes into a solvent containing 15 mL of deionized water and 35 mL of absolute ethanol, and ultrasonically treat to uniformly disperse the solute to obtain a high-entropy alloy precursor solution;

[0041] S3: Place the high-entropy alloy precursor solution obtained in step S2 in an oil bath at 90 °C and stir for 4 h to evaporate the solvent. Subsequently, perform freeze-drying, grind to obtain high-entropy alloy precursor powder. Take 50 mg of the high-entropy alloy precursor powder, tightly wrap it in a small piece of carbon paper, then place it on a carbon paper heater, and heat it using Joule heating technology. Heat at 300 °C for 0.5 s, and then continuously heat at 1000 °C for 1 s to obtain Co a Cu b Fe c Mn d Ni e Zn f high-entropy alloy nanoparticles. Tested by inductively coupled plasma atomic emission spectrometer, a is obtained as 26%, b is 25%, c is 6%, d is 4%, e is 38%, and f is 1%;

[0042] S4: Add 1 g of polyvinyl alcohol (PVA) to 9 ml of deionized water and dissolve it in an oil bath at 75 °C to obtain a 10 wt% PVA aqueous solution. Mix 1 mL of 10 wt% PPy aqueous solution, 0.5 g of high-entropy alloy nanoparticles, and 10 mL of 10 wt% PVA aqueous solution, and ultrasonically treat for 5 min to obtain a mixed solution. The mass ratio of PPy to PVA in the mixed solution is 1:10. Add 200 μL of 25 wt% glutaraldehyde solution and 100 μL of 2 M HCl aqueous solution, and continue ultrasonically treating for 5 min to obtain a composite hydrogel precursor;

[0043] S5: Let the composite hydrogel precursor obtained in step S4 stand overnight to promote gelation. Subsequently, freeze it at below -10 °C for 2 h and thaw it at 25 °C for 30 min. Repeat this cycle three times, and then place it in a freeze dryer and dry for 24 h to obtain a high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel.

[0044] Next, conduct material characterization and performance testing on this example, and the results are as follows:

[0045] As Figure 1 shown, use a scanning electron microscope to characterize the microtopography of the high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel prepared in Example 1. Analyze its surface microstructure by scanning electron microscope. As Figure 1 shown, it is found that the hydrogel presents a multi-scale pore structure, including wide gaps at the micron and nanometer levels, dividing the matrix into a highly interconnected porous framework. This hierarchical pore system effectively constructs a three-dimensional water transport network, where the micron-level main channels achieve rapid water replenishment, while the sub-micron-level pores maintain continuous wetting through capillary action, thereby synergistically optimizing the energy and mass transfer efficiency at the photothermal interface.

[0046] As Figure 2As shown, X-ray diffraction was used to analyze the phase of the Co 0.25 Cu 0.2 Fe 0.05 Mn 0.03 Ni 0.365 Zn 0.005 high-entropy alloy nanoparticles prepared in Example 1. As shown in the figure, obvious characteristic diffraction peaks appeared near 2θ of 40°, 50° and 70°, corresponding to the face-centered cubic structure, indicating that the synthesized product was a high-entropy alloy with a single solid solution phase. In addition, no obvious impurity phase peaks were observed in the spectrum, confirming the high phase purity of the product, and high-entropy alloy nanoparticles were successfully obtained.

[0047] As Figure 3 shown, a UV-Vis-NIR spectrophotometer was used to characterize the light absorption performance of the polyvinyl alcohol / polypyrrole composite hydrogel modified with the high-entropy alloy prepared in Example 1. The test results showed that in the wide spectral range of 280 - 2500 nm, the material exhibited excellent light trapping ability, and its average absorption rate reached 95%, showing excellent light absorption performance. This result indicated that the introduction of the high-entropy alloy significantly enhanced the light absorption ability of the hydrogel, thereby improving the efficiency of the solar interface evaporator.

[0048] As Figure 4 shown, the cyclic stability and light intensity dependence of the high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel-based evaporator prepared in Example 1 were tested. Under the light intensity of 1 kW / m 2 , the evaporation rate was 2.22 kg / (m 2 ·h), showing stable evaporation performance. When the light intensity was increased to 2 kW / m 2 , the evaporation rate increased significantly to 4.16 kg / (m 2 ·h), indicating that the photothermal conversion efficiency of the material was optimized with the increase of light intensity. When the light intensity was further increased to 3 kW / m 2 , the evaporation rate reached 6.68 kg / (m 2 ·h), verifying the adaptability of the material under high irradiation conditions. In the cyclic test, the evaporation rate showed reversible changes when the light intensity was switched, proving that the system had excellent stability.

[0049] Example 2

[0050] A high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material was prepared according to the following steps:

[0051] S1: It was basically the same as Example 1, except that 0.08 g of PPy powder was dissolved in 0.92 mL of deionized water, and after mixing, an 8 wt% PPy aqueous solution was obtained;

[0052] S2: It is basically the same as Example 1, except that in this example, the type of metal salt is changed from sulfate to chloride, and the volume ratio of the solvents is adjusted to 20 mL of deionized water and 30 mL of absolute ethanol. The specific dosages are as follows: 162.21 mg of ferric chloride, 130.83 mg of cobalt chloride, 129.59 mg of nickel chloride, 125.84 mg of manganese chloride, 136.28 mg of zinc chloride, 134.45 mg of copper chloride, and 50 mg of carbon nanotubes;

[0053] S3: It is basically the same as Example 1, except that the heating conditions are as follows: heating at 800 °C for 0.5 s, and then heating at 1500 °C for 1 s. Through this process, Co a Cu b Fe c Mn d Ni e Zn f high-entropy alloy nanoparticles, where a is 29%, b is 20%, c is 10%, d is 3.5%, e is 36.5%, and f is 1%;

[0054] S4: It is basically the same as Example 1, except that 1.5 g of PVA is added to 9 mL of deionized water to obtain a 15 wt% PVA aqueous solution; the mass ratio of PPy to PVA in the mixed solution is 1:15, and the mass ratio of high-entropy alloy nanoparticles to PPy is 1:15;

[0055] S5: It is basically the same as Example 1, except that the freezing temperature is -30 °C.

[0056] Example 3

[0057] Prepare a high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel material according to the following steps:

[0058] S1: It is basically the same as Example 1, except that 0.15 g of PPy powder is dissolved in 0.85 mL of deionized water and mixed evenly to obtain a 15 wt% PPy aqueous solution;

[0059] S2: It is basically the same as Example 1, except that in this example, the type of metal salt is changed from sulfate to nitrate, and the volume ratio of the solvents is adjusted to 25 mL of deionized water and 25 mL of absolute ethanol. The specific dosages are as follows: 241.88 mg of ferric nitrate, 182.95 mg of cobalt nitrate, 182.71 mg of nickel nitrate, 178.96 mg of manganese nitrate, 189.40 mg of zinc nitrate, 187.57 mg of copper nitrate, and 50 mg of carbon nanotubes;

[0060] S3: It is basically the same as Example 1, except that in this example, the heating conditions are as follows: maintaining at 300 °C for 3 s, and then maintaining at 1000 °C for 5 s. Through this process, Coa Cu b Fe c Mn d Ni e Zn f High-entropy alloy nanoparticles, where a is 27%, b is 22%, c is 5%, d is 6%, e is 38.5%, and f is 1.5%;

[0061] S4: Substantially the same as Example 1, except that 0.8 g of PVA was added to 9 mL of deionized water to obtain an 8 wt% PVA aqueous solution; the mass ratio of PPy to PVA in the mixed solution was 1:8, and the mass ratio of high-entropy alloy nanoparticles to PPy was 1:5;

[0062] S5: Substantially the same as Example 1, except that the freezing temperature was -40 °C.

[0063] Example 4

[0064] A high-entropy alloy-modified polyvinyl alcohol / polypyrrole composite hydrogel material was prepared according to the following steps:

[0065] S1: Substantially the same as Example 1, except that 0.12 g of PPy powder was dissolved in 0.88 mL of deionized water and mixed evenly to obtain a 12 wt% PPy aqueous solution.

[0066] S2: The same as Example 1;

[0067] S3: Substantially the same as Example 1, except that the heating conditions in this example were: heating at 800 °C for 3 s, and then heating at 1500 °C for 5 s. Through this process, Co was obtained a Cu b Fe c Mn d Ni e Zn f High-entropy alloy nanoparticles, where a is 27%, b is 23%, c is 5.5%, d is 3%, e is 40%, and f is 1.5%;

[0068] S4: Substantially the same as Example 1, except that 1.2 g of PVA was added to 9 mL of deionized water to obtain a 12 wt% PVA aqueous solution; the mass ratio of PPy to PVA in the mixed solution was 1:12, and the mass ratio of high-entropy alloy nanoparticles to PPy was 1:15;

[0069] S5: Substantially the same as Example 1, except that the freezing temperature in this example was -30 °C.

[0070] Example 5

[0071] Prepare a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material according to the following steps:

[0072] S1: Substantially the same as Example 1, except that 0.11 g of PPy powder is dissolved in 0.89 mL of deionized water, and after mixing, an 11 wt% PPy aqueous solution is obtained;

[0073] S2: Substantially the same as Example 1, except that in this example, the type of metal salt is changed from sulfate to chloride, and the solvent volume ratio is adjusted to 20 mL of deionized water and 30 mL of absolute ethanol. The specific amounts are: 162.21 mg of ferric chloride, 130.83 mg of cobalt chloride, 129.59 mg of nickel chloride, 125.84 mg of manganese chloride, 136.28 mg of zinc chloride, 134.45 mg of copper chloride, and 50 mg of carbon nanotubes;

[0074] S3: Substantially the same as Example 1, except that the heating conditions in this example are: 550 °C for 1.5 s, and then 1250 °C for 3 s. Through this process, Co a Cu b Fe c Mn d Ni e Zn f high-entropy alloy nanoparticles, where a is 28%, b is 21%, c is 9.5%, d is 4.5%, e is 35%, and f is 2%;

[0075] S4: Substantially the same as Example 1, except that 1 g of PVA is added to 9 mL of deionized water to obtain a 10 wt% PVA aqueous solution; the mass ratio of PPy to PVA in the mixed solution is 1:10, and the mass ratio of high-entropy alloy nanoparticles to PPy is 1:10;

[0076] S5: Substantially the same as Example 1, except that the freezing temperature in this example is -30 °C.

[0077] Example 6

[0078] Prepare a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material according to the following steps:

[0079] S1: Substantially the same as Example 1, except that 0.08 g of PPy powder is dissolved in 0.92 mL of deionized water, and after mixing, an 8 wt% PPy aqueous solution is obtained;

[0080] S2: It is basically the same as Example 1, except that in this example, the type of metal salt is changed from sulfate to nitrate, and the volume ratio of the solvents is adjusted to 25 mL of deionized water and 25 mL of absolute ethanol. The specific amounts are as follows: 241.88 mg of iron nitrate, 182.95 mg of cobalt nitrate, 182.71 mg of nickel nitrate, 178.96 mg of manganese nitrate, 189.40 mg of zinc nitrate, 187.57 mg of copper nitrate, and 50 mg of carbon nanotubes;

[0081] S3: It is basically the same as Example 1, except that in this example, the heating conditions are as follows: heating at 300 °C for 0.5 s, and then heating at 1500 °C for 5 s. Through this process, Co a Cu b Fe c Mn d Ni e Zn f high-entropy alloy nanoparticles are obtained, where a is 31%, b is 23%, c is 5.5%, d is 4%, e is 36%, and f is 0.5%;

[0082] S4: It is basically the same as Example 1, except that 1.5 g of PVA is added to 9 mL of deionized water to obtain a 15 wt% PVA aqueous solution; the mass ratio of PPy to PVA in the mixed solution is 1:15, and the mass ratio of high-entropy alloy nanoparticles to PPy is 1:15;

[0083] S5: It is basically the same as Example 1, except that in this example, the freezing temperature is -40 °C.

[0084] The evaporation rates of the polyvinyl alcohol / polypyrrole composite hydrogels modified with high-entropy alloys prepared in Examples 1-6 were compared under a light intensity of 1 kW / m 2 The results are as Figure 5 shown. The evaporation rate of Example 1 was the highest, at 2.22 kg / (m 2 ·h), while the evaporation rate of Example 6 was the lowest, at 2.04 kg / (m 2 ·h). Generally speaking, the evaporation rates of each example were relatively close, all between 2.04 kg / (m 2 ·h) and 2.22 kg / (m 2 ·h), indicating that the polyvinyl alcohol / polypyrrole hydrogel doped with high-entropy alloy has good evaporation performance under a light intensity of 1 kW. However, by adjusting the doping components and the preparation process of the hydrogel, its evaporation rate can be further optimized to meet the requirements of different application scenarios.

[0085] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation manner. The protection scope of the present invention shall be subject to the scope defined by the claims. Based on the above description, other different forms of changes or modifications can be made. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A preparation method of a polyvinyl alcohol / polypyrrole composite hydrogel material modified by a high-entropy alloy, characterized in that, It includes the following steps: S1: Dissolve ammonium persulfate in deionized water, and after mixing evenly, obtain an ammonium persulfate solution; Mix pyrrole monomer with deionized water to obtain a pyrrole solution. Under continuous stirring, drop the ammonium persulfate solution and the pyrrole solution into hydrochloric acid solution for polymerization reaction. After the reaction is completed, dry and grind to obtain polypyrrole powder. Dissolve the polypyrrole powder in deionized water, and after mixing evenly, obtain a polypyrrole aqueous solution; S2: Add iron salt, cobalt salt, nickel salt, manganese salt, zinc salt, copper salt and carbon nanotubes into deionized water and absolute ethanol, stir and mix evenly to obtain a high-entropy alloy precursor solution; S3: Heat and stir the high-entropy alloy precursor solution obtained in step S2 to evaporate the solvent, and then perform freeze-drying to obtain a high-entropy alloy precursor powder. Take the high-entropy alloy precursor powder, wrap it with carbon paper, and heat it by Joule heating technology to obtain high-entropy alloy nanoparticles; S4: Mix the polyvinyl alcohol aqueous solution, the polypyrrole aqueous solution obtained in step S1, and the high-entropy alloy nanoparticles obtained in step S3 to obtain a mixed solution. Add glutaraldehyde solution and hydrochloric acid solution to obtain a composite hydrogel material precursor; S5: Let the composite hydrogel precursor obtained in step S4 stand overnight, then perform freezing, and then thaw. Repeat the freezing-thawing cycle many times, and finally obtain a high-entropy alloy modified polyvinyl alcohol / polypyrrole composite hydrogel material after freeze-drying.

2. The preparation method according to claim 1, wherein In step S1, the concentration of the polypyrrole aqueous solution is 8-15 wt%.

3. The preparation method according to claim 1, characterized in that, In step S2, the iron salt, cobalt salt, nickel salt, manganese salt, zinc salt, copper salt are selected from one of sulfates, nitrates, and chlorides; the volume ratio of deionized water to absolute ethanol is 1:1-3:

1.

4. The preparation method according to claim 1, characterized in that, In step S3, the conditions for heating by Joule heating technology are: first heat at 300-800 °C for 0.5-3 s, and then heat at 1000-1500 °C for 1-5 s; The chemical formula of the high-entropy alloy nanoparticles is Co a Cu b Fe c Mn d Ni e Zn f , where a, b, c, d, e, and f are the percentage molar fractions of the six elements in the total metal content. a ranges from 26% to 31%, b ranges from 20% to 25%, c ranges from 5% to 10%, d ranges from 3% to 6%, e ranges from 35% to 40%, and f ranges from 0.5% to 2%. The sum of a, b, c, d, e, and f is 100%.

5. The preparation method according to claim 1, characterized in that, In step S4, the preparation method of the polyvinyl alcohol aqueous solution is: add polyvinyl alcohol to deionized water and stir at 70-90 °C to obtain a polyvinyl alcohol aqueous solution.

6. The preparation method according to claim 1, characterized in that In step S4, the concentration of the polyvinyl alcohol solution is 8-15 wt%.

7. The preparation method according to claim 1, characterized in that, In step S4, in the mixed solution, the mass ratio of polypyrrole to polyvinyl alcohol is 1:8-1:12, and the mass ratio of high-entropy alloy nanoparticles to polypyrrole is 1:5-1:

15.

8. The preparation method according to claim 1, characterized in that, In step S5, the freezing temperature is -10--40 °C, the freezing time is 2-3 h, the thawing temperature is 20-40 °C, the thawing time is 0.5-1 h, and the number of freezing-thawing cycles is 2-5 times.

9. The preparation method according to claim 1, characterized in that In step S5, the freeze-drying time is 12-24 h.

10. Application of the composite hydrogel material prepared by the preparation method according to any one of claims 1-9 in a solar interface evaporator.

Citation Information

Cited By

  • Composite hydrogel evaporator with chemical-photo-thermal synergistic antibacterial function and preparation of composite hydrogel evaporator

    CN120607302A

  • Chemical-photothermal synergistic antibacterial composite hydrogel evaporator and preparation thereof

    CN120607302B

  • Bipolar plate composite coating preparation method based on high-entropy alloy and conductive polymer

    CN121204768A

  • Preparation method and application of HEA@NCNTs composite photothermal evaporator

    CN122608132A